P255 Defining a circadian pattern of presentation of pulmonary embolism on CT/VQ imaging. (16th November 2010) - Shah, N; Jubber, A S; Syed, I
Abstract : Purpose: To evaluate whether there is an association between the chronological occurrence of pulmonary emboli, anatomical site, radiological extent and associated clinical risk factors. Materials and Methods: 1410 consecutive CTPA and VQ scans performed between December 2005 and October 2008 were retrospectively reviewed independently by 2 thoracic radiologists (kc=0.78). A third observer was used in equivocal cases. 270 cases of pulmonary emboli were identified. Records were available for 180 patients. 40 were excluded on the basis of incomplete presenting details. All diagnosed cases of pulmonary emboli were risk stratified according to the Wells score, underlying co-morbidities including diabetes, DVT, malignancy and cardiomyopathy. Morbidity, mortality and survival data were recorded. For 140 (Age 67 y SD ±17, 61 male), the occurrence of the pulmonary emboli based on onset of symptoms was defined by four time intervals. Each group was subdivided according to extent of clot. The average Wells score was calculated for each 6 h period. Results: 11% (n=16) patients presented between 00:00 and 06:00 h, 36% (n=50) between 06:00 and 12:00 hours, 30% (n=43) between 12:00 and 18:00, and 22% (n=31) between 18:00 and 24:00(χ 2 =18.3, p<0.05). Average Wells Scores were 4 (SD±2), 6 (SD±1), 4 (SD±2) and 5 (SD±2) for the respective times. Patients with bilateral emboli affecting the main pulmonary arteries were distributed as follows: 00:00–06:00 (n=2), 06:00–12:00 (n=17), 12:00–18:00 (n=10), 18:00–24:00 (n=9) (χ 2 =10.7, p<0.05). Patients with unilateral emboli affecting the main pulmonary arteries were found to present as follows: 00:00–06:00 (n=3), 06:00–12:00 (n=11), 12:00–18:00 (n=10), 18:00–24:00 (n=7) (χ 2 =5.00, p=0.17). Patients with bilateral emboli affecting the segmental arteries presented at: 00:00–06:00 (n=4), 06:00–12:00 (n=12), 12:00–18:00 (n=8), 18:00–24:00 (n=3) (χ 2 =7.52, p=0.05). Patients with unilateral emboli affecting the segmental arteries presented at: 00:00–06:00 (n=5), 06:00–12:00 (n=5), 12:00–18:00(n=8), 18:00–24:00 (n=5). (χ 2 =1.17, p=0.76) In the 4 time intervals, patients with >2 symptoms of chest pain, dyspnoea, or haemoptysis were found to be distributed as: 00:00–06:00 (n=8), 06:00–12:00 (n=26), 12:00–18:00 (n=16), 18:00–24:00 (n=17) (χ 2 =9.72, p<0.05). Conclusion: Pulmonary Emboli were most frequent between 06:00 and 12:00 h during which there was more extensive radiographical findings, associated with a higher Wells score, and more profound symptoms. This suggests a circadian pattern of the presentation of pulmonary emboli, correlating with the clinical and radiological severity of disease.